Myocarditis as a cause of neonate’s circulatory failure during delivery - case study - Pękała, Maciej; Stencel, Katarzyna; Berner, Aleksandra; Olszewska, Anna; Stelmaszak, Karina; Polak, Paulina; Polaszek, Monika; Bogowska, Marta; Matyja, Karolina; Marczyk, Klaudia (Journal of Education, Health and Sport, 2023)
Myocarditis (MCI) is a heart pathology characterized by its rare occurrence and a possible fatal course. In the natural history of the disease inflammatory cell infiltrates are present. There are subtypes of MCI depending on the predominant cell type in the biopsy sampls. One of them is eosinophilic myocarditis. In eosinophilic myocarditis more that 50% of the cells are eosinophils. In the later phases of the disease the myocardium is infiltrated by fibrous tissue and the heart vessels are often affected by thrombosis. Cardiomyopathy is a common long-term complication of the MCI. Reported case presents a death of a male neonate. The neonate was delivered by vaginal delivery. Both prenatal development and all the prenatal tests indicated proper development of the fetus. At the delivery the neonate weight was 3900 grams and was evaluated with only 1 point on the Apgar score. Moreover, the neonate presented a complete acute cardiorespiratory failure at birth. Despite the 2 hour-long cardio-pulmonary resuscitation no return of spontaneous circulation was observed. The neonate’s remains were pathologically as well as histologically examined. The microscopic examination of the neonate’s heart samples contained many inflammatory cell infiltrations. Microabscesses with Charcot-Leyden crystals inside were also observed. Furthermore, the presence of atypical, polynuclear cells was noted. On the basis of the morphological image, it was recognized as an eosinophilic MCI.